Rancang Bangun Kontrol Penerangan Rumah Menggunakan Media Bluetooth - Sumardi Sadi; Sri Mulyati (Sekolah Tinggi Teknik - PLN, 2019)
The design of home lighting controls using Bluetooth based Arduino nano is a prototype ON-OFF control device via a microcontroller and bluetooth which is activated with a smartphone that has an application installed android. The purpose of this study is to make a control device to control lights or LEDs with a shape quite simple with low cost, effective and efficient work. This prototype works perfectly. Tool distance with a smartphone working on a range of 1 meter to 10 meters (there is a barrier) and 11 meters (without barrier). The results of this experiment can be applied to ON and OFF the house lights by adding the Relay interface 220 Volt.